Quantitative in vivo CT arthrography of the human osteoarthritic knee to estimate cartilage sulphated glycosaminoglycan content: correlation with ex-vivo reference standards. Issue 6 (June 2016) - van Tiel, J.; Siebelt, M.; Reijman, M.; Bos, P.K.; Waarsing, J.H.; Zuurmond, A.-M.; Nasserinejad, K.; van Osch, G.J.V.M.; Verhaar, J.A.N.; Krestin, G.P.; Weinans, H.; Oei, E.H.G.
Summary: Objective: Recently, computed tomography arthrography (CTa) was introduced as quantitative imaging biomarker to estimate cartilage sulphated glycosaminoglycan (sGAG) content in human cadaveric knees. Our aim was to assess the correlation between in vivo CTa in human osteoarthritis (OA) knees and ex vivo reference standards for sGAG and collagen content. Design: In this prospective observational study 11 knee OA patients underwent CTa before total knee replacement (TKR). Cartilage X-ray attenuation was determined in six cartilage regions. Femoral and tibial cartilage specimens harvested during TKR were re-scanned using equilibrium partitioning of an ionic contrast agent with micro-CT (EPIC-μCT), which served as reference standard for sGAG. Next, cartilage sGAG and collagen content were determined using dimethylmethylene blue (DMMB) and hydroxyproline assays. The correlation between CTa X-ray attenuation, EPIC-μCT X-ray attenuation, sGAG content and collagen content was assessed. Results: CTa X-ray attenuation correlated well with EPIC-μCT ( r = 0.76, 95% credibility interval (95%CI) 0.64 to 0.85). CTa correlated moderately with the DMMB assay (sGAG content) ( r = −0.66, 95%CI −0.87 to −0.49) and to lesser extent with the hydroxyproline assay (collagen content) ( r = −0.56, 95%CI −0.70 to −0.36). Conclusions: Outcomes of in vivo CTa in human OA knees correlate well with sGAG content. Outcomes of CTa also slightly correlate with cartilage collagen content. Since outcomes of CTa are mainly sGAG dependent and despite the fact that further validation using hyaline cartilage of other joints with different biochemical composition should be conducted, CTa may be suitable as quantitative imaging biomarker to estimate cartilage sGAG content in future clinical OA research.